A Case of Recurrent Supratentorial Extraventricular Anaplastic Ependymoma in Adult - Seo, Sung Won; Kang, Ho Jun; Lee, Min Seok; Suh, Sang Jun; Lee, Yoon Soo; Lee, Jeong Ho; Kang, Dong Gee (Brain tumor research and treatment, 2019)
Supratentorial extraventricular anaplastic ependymoma (SEAE) in adults is a relatively rare intracranial tumor. Because of the very low prevalence, only a few cases have been reported. According to a recent study, SEAE is associated with a poor prognosis and there is no definite consensus on optimal treatment. We report a case of an adult SEAE patient who had no recurrence until seven years after a gross total resection (GTR) followed by conventional radiotherapy. A 42-year-old male had a persistent mild headache, left facial palsy, dysarthria, and left hemiparesis. Preoperative neuroimaging revealed an anaplastic astrocytoma or supratentorial ependymoma in the right frontal lobe. A GTR was performed, followed by adjuvant radiotherapy. Histologic and immunohistochemical results revealed anaplastic ependymoma. After seven years of initial therapy, a regular follow-up MRI showed a 3-cm-sized partially cystic mass in the same area as the initial tumor. The patient underwent a craniotomy, and a GTR was performed. Histopathologic examination revealed recurrence of the SEAE. External radiotherapy was performed. The patient has been stable without any disease progression or complications for 12 months since the surgery for recurrent SEAE.